Artificial Intelligence and Classroom Management in Education: Evolution of Academic Studies and Research Trends - Ay, Sevinc; Karabatak, Songul; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2025)
The transformative effect of technological developments in education has gained momentum with the development of artificial intelligence (AI). The integration of artificial intelligence into education has led to new areas of application, especially in classroom management. Technological developments and AI-supported systems make classroom management more efficient, allowing teachers to analyze student behavior and provide personalized education. Therefore, this study presents a bibliometric analysis of artificial intelligence and classroom management. VOSviewer, R studio Bibliometrix package and Gephi application were used for bibliometric analysis. Many analyses were applied on 388 data obtained from the Web of Science (WoS) database. After determining that there were publications between 1991-2025, Lotka's Law was used for author profile and network analysis. After presenting the findings on the most productive sources sub-dimension according to Bradford's Law, the source-author connection was shown with the Three-Field Plot. After the keyword analysis, content-based clustering analysis was performed and relevant articles were grouped into 6 clusters. The main themes related to the field were thus revealed. © 2025 IEEE.
13th International Symposium on Digital Forensics and Security, ISDFS 2025 -- 24 April 2025 through 25 April 2025 -- Boston -- 209331
Keywords: artificial intelligence; bibliometric analysis; classroom management